Invasive and Doppler Transvalvular gradients after transcatheter aortic valve replacement. (14th October 2021) - Fugar, S; Deka, K; Anderson, C; Lama Von Buchwald, C; Geroux, R; Al-Amoodi, M; White, J; Kavinsky, C
Abstract: Background: Differences in mean gradients after Transcatheter valve replacement (TAVR) vary depending on the valve type and the modality used to measure the gradients. Currently there is a paucity of data on the relationship between invasive and doppler derived gradients after TAVR. Purpose: We sort to assess the difference in doppler, and catheter derived aortic valve gradients after TAVR Methods: This is a single center retrospective study using consecutive patients who presented for TAVR on account of native aortic valve stenosis at our institution from May 2012 till December 2020. Patients with both intraoperative invasive and postoperative doppler derived pressure gradients were included in the analysis. Student T-test were used to compare mean gradients. Pearson's correlation test was used to examine the correlation between measured gradients. Results: A total of 587 patients were included in our study. Fifty one percent were male and 462 (78.7%) underwent TAVR with a balloon expandable valve. In the entire cohort the mean gradient measured invasively was significantly lower than those measured by echo doppler (4.48±3.25 vs. 5.57±3.11, P<0.001). There, however, was a positive correlation between invasive and doppler measured gradients (figure 1). In those who received balloon expandable valves, the invasive gradient was 4.39±3.30 and the doppler derived gradient was 5.47±3.04 (P<0.001), while in those self-expanding valves, the invasive gradient was 4.81±3.04 and doppler derived gradient was 5.94±3.36 (P<0.001). Conclusion: Post TAVR gradients were all significantly lower when measured invasively as compared to those measured using doppler. Self-expanding valves overall had higher residual gradients. Further studies are needed to assess the correlations between invasively measured gradients and clinical outcomes post TAVR. FUNDunding Acknowledgement: Type of funding sources: None.